Accounting and financial antecedents of corporate spin-offs in the lodging industry - Penela, D.; Estevão, J.; Gregory, A. M. (International Journal of Hospitality Management, 2019)
Lodging stocks have been gaining more attention from investors, likely due to the growth of the tourism sector (WTTC, 2017). However, limited research focuses on the financial behaviors of this market and prolific trends. The recent spin-offs of the timeshare business in major hotel chains, such as Marriott, Hilton, Starwood, and Wyndham have exposed an important research gap. Investors may know the reasons behind spin-offs, but they may also be able to predict them if they recognize certain conditions, namely, a firm will spin-off if a combination of conditions is met. Thus, this research provides six configurations of accounting and financial variables that lead to a spin-off in the lodging industry. Findings indicate that depending on the motivation behind a spin-off, certain combinations of variables can be recognized, and a spin-off could be predicted. Practical implications are then clear, as stock investment decisions may be influenced by this prediction.